Profil Berpikir Siswa MI Dalam Pemecahan Masalah Pecahan Ditinjau dari Gaya Belajar - Khurin’in Ratnasari Ratnasari (STAIFAS-Press, 2018)
ABSTRACT This paper aims to describe the profile of thinking of MI students in solving fraction problems in terms of learning styles. In this paper the visual subject and subject of Audiotori are the same about how to understand the problem by reading the problem in a slow or loud voice as much as once or repeatedly, expressing the problem in their own words, repeating things that are known and explaining according to their own language, given other knowledge that has been it has or a concept that has been mastered to make a plan that is by adding it up and remembering the plan that has been made by raising the idea to start working on the problem of the problem given, make a plan that will be used in solving the problem by implementing the plan made, storing information that is by saying repetitive plans made and repeating the implementation of the plan. Keywords: profile thinking, algebra problem solving, learning style.